Cross-phyla protein annotation by structural prediction and alignment - Ruperti, Fabian; Papadopoulos, Nikolaos; Musser, Jacob M.; Mirdita, Milot; Steinegger, Martin; Arendt, Detlev (Genome biology, 2023)
Protein annotation is a major goal in molecular biology, yet experimentally determined knowledge is typically limited to a few model organisms. In non-model species, the sequence-based prediction of gene orthology can be used to infer protein identity; however, this approach loses predictive power at longer evolutionary distances. Here we propose a workflow for protein annotation using structural similarity, exploiting the fact that similar protein structures often reflect homology and are more conserved than protein sequences.